Effect of natural antioxidants on the oxidation stability of methyl ester of rubber seed oil. Issue 6 (19th March 2018) - Narayanasamy, Bose; Jeyakumar, Nagarajan; Manoharan, Dinesh Kumar
ABSTRACT: Biodiesel has been proved as a promising solution amidst other alternate fuels in terms of its characteristics compared to diesel. The oxidation property of biodiesel results in the degradation of its quality. This problem can be solved by the addition of suitable antioxidants which improves the oxidation stability of the fuel. Usage of natural antioxidants offsets the defects in synthetic antioxidants, because they are renewable, nontoxic as well as cost effective. The effect of natural antioxidant additives on the oxidation stability of the Methyl Ester of non-edible Rubber Seed oil (MERB) has been experimentally investigated in this study. Natural antioxidants Ginger, Moringa oleifera Lam, Basil and Oregano have been mixed in varying proportions (500, 1000, 1500 and 2000 ppm) and the antioxidant characteristics of the additives were identified by using Fourier Transform Infra-Red (FTIR) analysis. The induction period, which denotes the oxidation stability was worked out with Rancimat apparatus. From this study it was found out that the oxidation stability of MERB increased when natural antioxidant additives were added. Among the antioxidants used, Ginger was found to be more effective in enhancing the oxidation stability, with induction period values of 11.5 h, 18.5 h, 23 h and 26.5 h for proportions 500, 1000, 1500 and 2000 ppm respectively.